Total Glucosides of Paeony Alleviate Cell Apoptosis and Inflammation by Targeting the Long Noncoding RNA XIST/MicroRNA-124-3p/ITGB1 Axis in Renal Ischemia/Reperfusion Injury - Fang Chen; Yi Hu; Yuetao Xie; Zonghui Zhao; Lin Ma; Zhili Li; Wanlong Tan (Hindawi Limited, 2020)
Objective. Renal ischemia/reperfusion injury (RI/RI) is the main cause of acute kidney injury. Total glucosides of paeony (TGP) are a traditional Chinese medicine. This study was aimed at exploring the role of TGP in RI/RI and its underlying mechanism of action. Methods. Rat RI/RI models were constructed by surgical operation. Serum creatinine (Scr) and blood urea nitrogen (BUN) were used to evaluate renal function. The levels of proinflammatory cytokines were detected by ELISA. RI/RI was simulated by hypoxia/reoxygenation (H/R) treatment in renal cells in vitro. The lncRNA XIST (XIST) expression was analyzed by qRT-PCR. Then, the viability and apoptosis of renal cells were detected by MTT and flow cytometry assay. Additionally, dual-luciferase reporter assay was used to determine the interactions among XIST, microRNA-124-3p (miR-124-3p), and ITGB1. Results. TGP improved renal function and inhibited inflammatory responses after RI/RI. XIST expression was highly expressed in rat RI/RI models and H/R-treated renal cells, whereas treatment with TGP downregulated the XIST expression. Additionally, TGP increased viability and attenuated apoptosis and inflammation of H/R-treated renal cells via inhibiting XIST. Moreover, XIST was competitively bound to miR-124-3p, and ITGB1 was a target of miR-124-3p. miR-124-3p overexpression or ITGB1 inhibition rescued the reduction effect on viability and mitigated the promoting effects on cell apoptosis and inflammation caused by XIST overexpression in H/R-treated renal cells. Conclusions. In vivo, TGP attenuated renal dysfunction and inflammation in RI/RI rats. In vitro, TGP inhibited XIST expression to modulate the miR-124-3p/ITGB1 axis, alleviating the apoptosis and inflammation of H/R-treated renal cells.